Design of disassembly-to-order system for reused components and recycled materials using linear physical programming. (23rd April 2020) - Kinoshita, Yuki; Yamada, Tetsuo; Gupta, Surendra M.
To reduce the consumption of natural resources, a disassembly-toorder (DTO) system is required, where end-of-life (EOL) products are purchased and disassembled for component reuse and material recycling. A DTO system involves multiple uncertainties due to different qualities of EOL products. These uncertainties make it difficult to determine the number of take-back EOL products from suppliers to reuse, recycle, or send to disposal facilities, in order to satisfy multiple goals. To solve the multi-criteria DTO problem, linear physical programming (LPP) is used. LPP can seek a solution to satisfy preferences of a decision maker with respect to each criterion. This study attempts to achieve higher aspiration levels for multiple goals simultaneously in a DTO system by using LPP. A numerical example is conducted with three different EOL products composed of eight different components. It is found that only three components need to be procured from an outside components supplier to satisfy the demands by determining the number of purchased EOL products from the suppliers in the numerical experiment.